Transgenders in the current debate on identity policies: (de) constructions and tensions to the heteronormative paradigm in Brazil. - Amanda Pereira de Carvalho Cruz; Sandra Maria Nascimento Sousa (Travessias, 2018)
Transgender is a term commonly used to talk about the multiplicity of subjects who experience their subjectivity through identifying processes that evade biologically and culturally determined normativity. However, such terminology has a tense debate, since it produces a category that constitute an organized identity between social groups, but it can also produce exclusion and generalization. Discussing the term trans and its derivations (transex, transgender, etc.) is not only a critique to possibles reductionisms, but an alert of not falling into traps. Seeking to understand processes of social identity is interesting for the achievement of social rights. However, it is important to understand how each person names themselves and what is relevant to them. How your experience can be unique and particular. This work aims to discuss the terminologies used to describe subjects' experiences in the midst of transgressions, differentiations and ruptures to heteronormative references, in the main the terms transgender and transgenerity. We define our framework from theoretical approaches with Post-structuralism, considering that all discursive formation permeates linguistic regularities mixed according to strategic power games, involving exclusion procedures composed of interdictions, separations and the will of truth, in which the inconsistencies structures do their own dismantling. We propose that the uses of identity categories are not random. The need for collective identities can facilitate democratic articulation and raise issues that generate critical weight within social rights vis-à-vis public power.